Evaluation of Primary School Teachers’ knowledge and Role Regarding Asthma Management in Almatamma Village - Elnageeb, Mariam Mohammed; Mohmmed , Shireen abdelfatah; Ali , Fatima Osman (IJRDO- Journal of Educational Research, 2019)
This study was performed in Almatamma village to assess the primary school teacher’s knowledge and role regarding asthma management, in the period from July to November 2017. Data was collected by questionnaire, 70 teachers were participated in the study. The study revealed that teachers’ knowledge regarding asthma symptoms was inadequate, but they had good attitude regarding asthma management in case of asthma attack. The educational level and years of experience of the teachers did not affect their knowledge about asthma. Study recommended planning and implementing of training courses and workshops to increase teachers’ knowledge about asthma and its management, to encourage all schools to develop specific places to safe the students in case of asthmas attack, and to train teachers about the triggers factors and proper use of metered dose inhaler.